Economies of Justice: Workers and Labour Reformers in Late-Victorian Canadian Industrial Fiction - Janes, Daniela Alexandra (University of Toronto, 2004)
In this dissertation I propose the existence of a distinct and previously unacknowledged sub-genre in the Canadian social-reform writing of the 1890s, namely the industrial novel. I concentrate on several late-Victorian Canadian examples: Agnes Maule Machar's Roland Graeme: Knight: A Novel of Our Time (1892), Robert Barr's The Mutable Many (1896), and Albert Richardson Carman's The Preparation of Ryerson Embury: A Purpose (1900). These novels each reflect the expansion of industrial production in the Victorian period and the concomitant social effects of urban industrialism upon the labouring poor. I undertake an examination of these works that analyses the relationship between the novels' middle-class protagonists and the workers whose rights they are defending, seeing in the narrative patterns, imagery, and intertextual references both the articulation of an alternative kind of social justice and a tension emerging between political dissent and political conservatism. These novels of labour unrest caution against violent revolution and instead preach a doctrine of reconciliation and compromise, rooted in a reorientation of conventional notions of justice, a rejuvenation of social institutions, and the imperative of individual moral responsibility. First I focus on Machar's representation of Christian socialism, and how the language of "brotherhood" acts as an antidote and alternative to the morally degenerative effects of industrialism. Machar parallels the labour reform movement to the Christian belief in an afterlife: both are predicated upon faith and deferral, the commission of good works in the present for the benefit of some future blessing. Next, I examine Barr's novel about two strikes in a London factory, looking in particular at issues of leadership and representation. I propose that his novel works to reveal the complexities inherent in any project in which one man must speak for a crowd of others, as the end of the novel amply deconstrates the failure of communication. Finally, in my examination of Carman's novel, I analyse his refashioning of conventional notions of justice. I argue that Carman's narrative suggests the sterility of intellectual debate in the absence of any commitment to social action. I conclude by connecting the late-Victorian Canadian industrial novel to early twentieth-century literary responses to labour advocacy, urbanism, and industrialism.
Keywords: Agnes Maule Machar; Albert Richardson Carman; Industrial fiction; Labor reform; Language; Robert Barr; Workers; literature and linguistics